Investing in China and Chinese Investment Abroad - Zhang, Xiuping (Springer Singapore, 2018)
The book provides a study of the investment environment for international enterprises in China and overseas investment by Chinese enterprises. Applying statistical methods and up-to-date data analysis, it examines every aspect of the investment environment in China. The author's ideas are further illustrated with 39 figures and diagrams. Its 18 chapters discuss topics ranging from history, the current situation and problems of foreign investment in China, to China's policies for attracting foreign investment, the top 500 global companies in China, urban competitive analysis and multinational corporations in Beijing. It also analyzes Chinese investment in foreign countries. It is a valuable investment guide, and is also a useful reference resource for academic research and teaching related to international business and the Chinese economy.